2021
DOI: 10.1128/mcb.00668-20
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Proteins PCBP1 and PCBP2 Are Critical Determinants of Murine Erythropoiesis

Abstract: We have previously demonstrated that the two paralogous RNA binding protein, PCBP1 and PCBP2, are individually essential for mouse development: Pcbp1 -null embryos are peri-implantation lethal while Pcbp2 -null embryos lose viability at mid-gestation. Mid-gestation Pcbp2 −/− embryos revealed a complex phenotype that included loss of certain hematopoietic determinants. Whether PCBP2 directly contributes to erythropoietic differentiation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Conditional inactivation of Pcbp1 or Pcbp2 individually in the erythroid lineage using EpoR-Cre failed to significantly impact the development of the erythroid lineage, while the combined conditional inactivation of Pcbp1 and Pcbp2 results in the loss of hematopoiesis and blunted erythroid development. These results suggest that Pcbp1 and Pcbp2 serve redundant roles in the development of the erythroid lineage 22 . Interestingly, despite the redundancy of Pcbp1 in erythroid development, the expression of Pcbp1 alone is sufficient for erythroid heme and globin production postnatally 17 .…”
Section: Introductionmentioning
confidence: 81%
“…Conditional inactivation of Pcbp1 or Pcbp2 individually in the erythroid lineage using EpoR-Cre failed to significantly impact the development of the erythroid lineage, while the combined conditional inactivation of Pcbp1 and Pcbp2 results in the loss of hematopoiesis and blunted erythroid development. These results suggest that Pcbp1 and Pcbp2 serve redundant roles in the development of the erythroid lineage 22 . Interestingly, despite the redundancy of Pcbp1 in erythroid development, the expression of Pcbp1 alone is sufficient for erythroid heme and globin production postnatally 17 .…”
Section: Introductionmentioning
confidence: 81%
“…Among the motifs enriched in 5′ UTRs, we find for example the consensus binding sequence for the translational regulators IGF2BP2 (AMAWACA motif) and PCBP2 (CCUYCCC motif). IGF2BP2 is a mouse embryonic RBP shown to directly bind the 5′ UTR of target transcripts (Dai et al , 2011; Dai et al , 2015; Nielsen et al , 1999), and PCBP2 is a translational inhibitor acting via 5′ UTR-binding involved in mouse erythropoietic differentiation (Ji et al , 2021; Smirnova et al , 2019). Other motif-matching RBPs have been described to bind the 3′ UTR of target transcripts to regulate translation, such as Lin28A (HGGAGAA motif) and HuR (UUUUUUU and UUUGUUU motifs).…”
Section: Discussionmentioning
confidence: 99%
“…However, PCBPs might indirectly regulate enterocyte iron levels by (a) delivering iron to PHDs that in turn modulate intestinal HIF-2α levels and (b) PCBP2 binding to both DMT1 and Fpn1 to promote iron cellular uptake [ 34 ]. More recently, it was shown that PCBP1 and 2 are essential genes for mouse development [ 35 ] and erythroid differentiation [ 36 ]. In addition, PCBP1 and nuclear receptor co-activator 4 (NCOA4) co-operatively regulate erythroid iron storage and erythropoiesis (discussed below).…”
Section: Cytosolic Chaperones For Delivering Iron Into Ferritinmentioning
confidence: 99%